Pain in non-communicative older adults beyond dementia: a narrative review - Tagliafico, Luca; Maizza, Giada; Ottaviani, Silvia; Muzyka, Mariya; Rovere, Federica Della; Nencioni, Alessio; Monacelli, Fiammetta (Frontiers in Medicine, 2024)
Aging is associated with an increased risk of developing pain, especially in the presence of concurrent chronic clinical conditions. Similarly, multimorbidity can affect the perception and ability of older adults to appropriately respond to and communicate pain, and there is a clinical heterogeneity in the processing of painful sensations in different neurological conditions. The present narrative review is aimed at assessing the prevalent diseases associated with poor communication and pain in older adults, together with the available diagnostic instruments for the clinical assessment of pain in such a vulnerable population. Dementia was the most described pathology identified in the current literature associated with poor communication in older adults affected by pain, along with Parkinson’s disease and stroke. Notably, a common pattern of pain behaviors in these neurological disorders also emerged, indicating potential similarities in the clinical presentation and appropriate diagnostic workout. At the same time, there are many differences in the way patients express their pain according to their main neurological pathology. In addition to this, although a plethora of observation-based tools for pain in patients with dementia have been developed, there is no gold standard, and the clinical utility of such measurements is still largely unaddressed. Meanwhile, there is substantially no standardized observation-based tool for pain in non-communicative patients with Parkinson’s disease, and only a few for stroke. Overall, the present narrative review provides an update on the prevalent diseases beyond dementia associated with a communicative disability and a painful condition in older adults.